Elemental concentrations of ambient particles and cause specific mortality in Santiago, Chile: a time series study - Valdés Ana; Zanobetti Antonella; Halonen Jaana I; Cifuentes Luis; Morata Diego; Schwartz Joel (BMC, 2012)
Abstract Background The health effects of particulate air pollution are widely recognized and there is some evidence that the magnitude of these effects vary by particle component. We studied the effects of ambient fine particles (aerodynamic diameter < 2.5μm, PM2.5) and their components on cause-specific mortality in Santiago, Chile, where particulate pollution is a major public health concern. Methods Air pollution was collected in a residential area in the center of Santiago. Daily mortality counts were obtained from the National Institute of Statistic. The associations between PM2.5 and cause-specific mortality were studied by time series analysis controlling for time trends, day of the week, temperature and relative humidity. We then included an interaction term between PM2.5 and the monthly averages of the mean ratios of individual elements to PM2.5 mass. Results We found significant effects of PM2.5 on all the causes analyzed, with a 1.33% increase (95% CI: 0.87-1.78) in cardiovascular mortality per 10μg/m3 increase in the two days average of PM2.5. We found that zinc was associated with higher cardiovascular mortality. Particles with high content of chromium, copper and sulfur showed stronger associations with respiratory and COPD mortality, while high zinc and sodium content of PM2.5 amplified the association with cerebrovascular disease. Conclusions Our findings suggest that PM2.5 with high zinc, chromium, copper, sodium, and sulfur content have stronger associations with mortality than PM2.5 mass alone in Santiago, Chile. The sources of particles containing these elements need to be determined to better control their emissions.